TINJAUAN KREATIVITAS RETORIKA VISUAL POSTER FANART BOYBAND “BTS” OLEH A.R.M.Y PADA PLATFORM PINTEREST - Mulan; Sudjadi Tjipto Rahardjo (AKSA: Jurnal Desain Komunikasi Visual, 2021)
Poster is a promotional media that are set in a public with the aim of seeking attention of the masses as strongly as possible. Over technological developments, posters can be distributed through the internet and then creativity showed up from many fandoms; especially ARMY, in re-creating posters, this is commonly referred as fan art. The purpose of this research is to find out the creativity and variety of visual rhetoric in that fan art posters. The theory used in this research is theory of Visual Rhetoric. This research uses a qualitative approac, with data collection techniques through the internet and literature study. The results of this study indicate that there are the differences elements between the original poster with the fan art. And the results of this study also showed that the 2 posters which analyzed had the different verbal and visual rhetoric from one to another.